Engineering a Secure and Traceable System for Diploma Issuance in a Brazilian Federal Institution - Gonçalves, J. L. S.; Riça, A. R.; Amorim, W. F.; Figueiredo, N. S.; Oliveira, S. S.; Campelo, D.; Cunha, L. M. (Anais do Workshop de Sistemas de Informação (WSIS); 2025: Anais do XVI Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2025.15365, 2025)
The issuance of academic diplomas in Brazilian federal institutions remains a significant administrative challenge, affected by manual workflows, lack of standardization, and limited security mechanisms. These weaknesses result in slow processing, rework, and exposure to fraud, reflecting broader barriers in the digital transformation of the public sector. In response to these issues, the Ministry of Education mandated the nationwide adoption of secure and standardized digital diploma systems. However, implementation has been hindered by institutional heterogeneity and a lack of integrated tools. This work presents the design and implementation of a secure, auditable, and regulation-compliant system for diploma issuance, developed under the XP1 agile methodology. The system automates both physical and digital diploma generation, integrates with academic platforms, enforces role-based access control, and maintains detailed audit logs to support accountability. The project was conducted over 24 weeks in a real institutional context, with iterative deliveries and active collaboration with administrative staff. Validation involved empirical trials and structured feedback from diploma officers. Results demonstrated a 78.7% reduction in issuance time, fewer operational errors, and high user acceptance.